Influence Multiplication, Substitution and Factors Friends Against Function Limits Algebra Class XI - Saputra, Yudi (PPSDP International Journal of Education, 2024)
This research aim for test influence mastery multiplication between tribe, concept factor friends, and substitution direct to determination function limit value with use factor companions and substitutes direct. Method used is analysis simple linear regression with hypothesis that has been formulated. Analysis results show that there is influence significant between mastery multiplication between tribe, concept factor friends, and substitution direct to determination function limit value. The stated hypothesis exists influence mastery multiplication between tribe, concept factor friends, and substitution direct to determination function limit value accepted based on results analysis simple linear regression. Next, analyze multiple linear regression show that mastery multiplication between tribe, concept factor friends, and substitution direct in a way together is also influential significant to determination function limit value. In conclusion, the novelty of this study is disclose outlook just the previous one Not yet revealed about influence mastery multiplication between tribe, concept factor friends, and substitution direct. Highlighting approach new in determine function limit value through multiplication factor companions and substitutes direct. This study in a way special conducted in class XI Science at SMA Negeri 20 Palembang, giving relevant findings and implications with context education local. Research result This support hypothesis that mastery multiplication between tribe, concept factor friends, and substitution direct own influence to determination function limit value with use factor companions and substitutes direct.